TIAA-CREF. (A), A pension giant takes a hard look at serving the customer - Rosenthal, Jean W., 1945- (SAGE knowledge. Cases., 2016)
Founded as TIAA in 1918 to help academics avoid poverty after retirement, TIAA-CREF had grown to a Fortune 100 company, managing over $260 billion in assets for 3.2 million participants. However, for a company with so many assets and so many individual customers, TIAA-CREF was not well known. This case examines Herb Allison's attempts to diversify the company beyond its primary products.